2006
DOI: 10.1111/j.1365-2761.2006.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effect of mushroom glucan and bovine lactoferrin upon Aeromonas hydrophila vaccination in catla, Catla catla (Hamilton)

Abstract: Mushroom glucan and bovine lactoferrin (Lf), known for their immunostimulatory potential, were used as adjuvant in conjunction with a formalin-killed Aeromonas hydrophila vaccine in catla, Catla catla. In vitro antigen-specific responsiveness of catla leucocytes and protective responses against experimental challenge with homologous antigen were monitored following immunization. Antigen-specific proliferation, 'macrophage activating factor' (MAF) production and antibody production were significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 23 publications
3
34
1
5
Order By: Relevance
“…This might be due to polyclonal activation of leukocyte already sensitized with the antigen. Similar antigen-specific proliferative responses have also been reported in catla [24] and other fish species [25,26]. Significantly higher proliferative response by FE þ A group compared to the control group demonstrated higher efficacy of the vaccine when it was mixed with adjuvant.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This might be due to polyclonal activation of leukocyte already sensitized with the antigen. Similar antigen-specific proliferative responses have also been reported in catla [24] and other fish species [25,26]. Significantly higher proliferative response by FE þ A group compared to the control group demonstrated higher efficacy of the vaccine when it was mixed with adjuvant.…”
Section: Discussionsupporting
confidence: 72%
“…The challenge study did not reveal a good degree of protection against A. invadans in all the vaccinated groups. Reports are available to draw relationship between antibody production and protection [24,33,34]. The present study showed significant antibody production but the protection against A. invadans challenge was not significant enough.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In Indian carp Catla catla (Hamilton 1822), bLF-adjuvanted vaccine against Aeromonas hydrophila is able to enhance the Ab agglutination titre, although this does not confer better protection following experimental challenge (Kamilya et al 2006).…”
Section: Introductionmentioning
confidence: 99%